Inter-country effects from the internationalisation of higher education services: theoretical and empirical analysis - Paulava, Natalia S.; Danilchanka, Alexey V. (Journal of the Belarusian State University. Economics, 2021)
Considering the active growth of international student mobility in recent years, there exists an important question of measuring the economic impact of internationalisation for hosting and sending countries. Borrowing Bergerhoff’s two-country model for measuring effective capital formation under the condition of existence of international education, the effects of internationalisation of higher education services for Belarus and the European Union were investigated. The results of the study showed that internationalisation of higher education is beneficial to the country that hosts international students and is able to retain them after graduation. And the country that sends its students to study abroad also receives an increase in economic growth if the productivity of education in a foreign country is higher and some of the students return home after graduation.